Kualitas fisik telur ayam ras yang direndam dalam larutan teh hijau (Camellia Sinensis) komersial - Tooy, M.D; Lontaan, N.N.; Karisoh, L.C.M.; Wahyuni, I. (ZOOTEC, 2021)
PHYSICAL QUALITY OF EGGS DIPPED IN A COMMERCIAL GREEN TEA (Camellia sinensis) SOLUTION. Studies conducted to determine and understand the physical quality of broiler eggs soaked in commercial green tea solution. The variables observed were the decrease in egg weight, protein index, egg yolk index and Haugh unit. This study used a fully randomized design (CRD) with 5 treatments as follows: P0 = no immersion, P1 = green tea solution concentration 40%, P2 = green tea solution concentration 50%, P3 = green tea solution concentration 60% , P4 = concentration of the green tea solution 70% with 4 repetitions. The results showed that the immersion of the commercial green tea solution was not significant (P> 0.05) from the egg yolk index and Haugh Unit index, but significant (P <0.05) from the decrease in egg weight and protein index. The average reduction in egg weight had the lowest value at a concentration of 50% with a value of 3.91% and the highest value at no immersion with a value of 5.40%. The protein index had the highest value at a concentration of 40%, namely 0.13 compared to the concentration of other solutions and without immersion. The egg yolk index has the highest average value at a solution concentration of 40% with a value of 0.16 compared to the concentration of other solutions or without immersion. Haugh Unit has the highest average value at a solution concentration of 40% with a value of 51.64 and compared to the concentration of other solutions and without immersion. Eggs soaked in a commercial green tea solution can suppress the physical quality of chicken eggs at a concentration of 40% and are more effective than other commercial green tea solutions.Keywords: eggs, green tea, physical quality.